Sri Aman District Office / Lisa Richard - Richard, Lisa (Universiti Teknologi MARA, Sarawak, 2018)
Sri Aman District Administration is an organization which is capable to deliver a good quality of services to their customer. The organization is District Office of Sri Aman Division. Besides, Sri Aman have two sub-district office under its administration which are Pantu Sub-Office and Lingga Sub-Office. Sri Aman District Office is under administration of Sri Aman Resident Division where Mr Jonathan Lugoh as an officer of Sri Aman Resident Division since 2011 to 2017. In April 2017, the position for the officer of Sri Aman Resident Division have been taken over by Mr Indit Bangai until now. Simanggang District Administration or known as Sri Aman today was introduced as early years of 1846 as soon as ‘Wilayah Lupar’ handed over to James Brooke. Sri Aman District was under Sri Aman Division that is at South of Sarawak. According to the new delimitation in the Year of 2002. Its covers all the entire valley of ‘Batang Lupar’ which extends from Lingga to Hulu Skrang and the other flow of strean except ‘Batang Ai’. Sungai Batang Ai was located at Lubok Antu District. The new delimitation has been done after Maludam Sub-District handed over under the administration of Belong Division. Sri Aman District Office has been launched on 27 May 1970 by Chief Minister of Sarawak. Dato Penghulu Tawi Sli, on that time. Now, Mr Ismawie Bin Salleh is a District Officer of Sri Aman Division and the office have 17 staffwhich includes from different races in the year of 2016.